THE EFFECT OF PROTECTIVE TAEKWONDO FOOTPADS ON ATTENUATING IMPACTS OF AN INSTRUMENTED HEAD-FORM. Issue 7 (11th March 2014) - Fife, G; O'Sullivan, D; Pieter, W; Lee, S
Abstract : Background: A recent regulation in boxing, of removing headgear, proposes the question as to whether a similar rule should be adopted in taekwondo. Objective: To assess the effect of protective taekwondo footpads on attenuating impacts of an instrumented head-form. It is hypothesised that footpads with greater thickness would mitigate impacts better than thinner ones. Design: Between groups. Setting: Impact biomechanics laboratory. Participants: World Taekwondo Federation approved protective footpads. Risk factor assessment: A standardized (ASTM F-2397) martial arts headgear striker was used to impart impacts to a 50th Percentile Male Hybrid III head and neck complex. All impacts were imparted with a terminal striking velocity of 5.0 m/s (min-max: 4.75–5.15 m/s). Six different striking conditions were employed (no footpad (control), KDS, Adidas, Mooto, Mooto MTX, old style footpad [i.e., thick]). Each footpad condition was tested for a total of 3 impacts. The level of significance was set to an effect size of 0.2. Main outcome measurements: Resultant linear acceleration (RLA). Results: Significant differences were found between all footpads (eta 2 =0.86). The most effective impact attenuation was provided by the old style footpad (102g), followed by the Adidas (124g), KDS (140g), Mooto (140g), MTX (149g), and non-footpad condition (211g). The greatest difference in RLA was observed between the thick footpad and the non-padded condition (102 g v 211 g, d=2.08, 95% CI=-0.19–3.51). Conclusions: The footpads when compared with the control condition did decrease the RLA but not to an ASTM standard of 50g. These results do not support the removal of protective taekwondo headgear. Future studies may investigate the use of better designed footpads if a similar regulation were to be adopted.